PERBEDAAN KEBERHASILAN MODEL PEMBELAJARAN SAINS TEKNOLOGI MASYARAKAT DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP PENINGKATAN RANAH KOGNITIF PESERTA DIDIK - Pradana, Rego (Jurnal Pendidikan Geografi Gea, 2016)
Learning activity can be developed by making various activity in the class. The learning activity can make student more dominant in the classroom. It can be done by using various learning models that can improve student to study means. With the result that cognitive of student can be improve. This research aims to see differences from learning models of science technology society with learning model problem based learning. The method that is used in this research is quasi experimental design with research design nonequivalent Pretest-Posttest Control Group Design. To get the data is done with cognitive test (pretest and posttest), and also observation sheets to see learning activity. Technique of analyzing the data use statistic test normalize, homogeny and test T with helping of SPSS Statistic 21. Besides that, this research analyzes enhance cognitive students, and analyze successful of learning model science technology society and learning model problem based learning. The result of this research shows that learning model science technology society and learning model problem based learning can improve students cognitive. The conclusion from this research is learning model problem based learning and learning model science technology society are successful to improve students cognitive in State Senior High School 1 of Kroya. Meanwhile Learning model of problem based learning is more successful to improve students cognitive better than Science technology society model.Keywords: Learning model of science technology society, Learning model of problem based learning, Improvement cognitive.